GFL Lessons of the Future: Introduction of the Pluricentric Concept on the Example of Austrian Films - Utri, Reinhold (Germanistinnen und Germanisten im Beruf – zwischen Ausbildung und Realität, 2020)
Even when traveling, schoolchildren become aware that there are both national (pluricentric) and regional (dialect) variations in the German-speaking countries, which they did not get to hear / learn in their GFL lessons. Most teachers continue to use standard German (represented by the general Duden and the Aussprache-Duden). The purpose of this article is to show that it is not difficult to give students an insight into the different varieties; this should be shown using the example of Austrian films.